An Evaluation of the capability of Gauteng's Provincial academic/tertiary hospitals to manage an infectious disease outbreak - Nathan, Rita (University of Limpopo (Medunsa Campus), 2009)
The threat posed by infectious diseases is progressively growing on a global scale. With 2010 rapidly approaching, when South Africa will host the Soccer World Cup, there will be a massive influx of foreigners into the country. The purpose of the study was evaluate to the status of Gauteng tertiary academic hospitals with respect to outbreak response and, with the help of existing local and international policies and research, to develop a generic model that can be used by hospitals in developing outbreak response policies and standard operating procedures. Methods A descriptive cross-sectional survey using a semi-structured questionnaire was utilized to evaluate the preparedness of tertiary health care facilities in South Africa. The target population consisted of Clinical Directors, Senior Clinical Executives/ Medical Superintendents, Infection Control Nurses and / or Quality Assurance Managers and Infection Control Nurses. These categories of health professionals were targeted as they are normally delegated responsibility for outbreak response activities. Results Twelve tertiary academic hospitals were included in the survey and nine responded to the survey questionnaire giving a 75% response rate. Other significant findings were: • 71% of the responding hospitals had clear terms of reference for their response team. v • 43% of the responding hospitals had a functional preparedness and response strategy / plan for priority diseases. • The most frequent point of entry in the tertiary academic hospitals is the casualty / emergency unit, followed by the trauma and OPD areas • There are very few ‘protective environment wards’ and ‘airborne infection isolation rooms’ in Gauteng Province. • Only 15% of responding hospitals have infection control compatible ventilation and only 42% could manage a patient that requires quarantine in the casualty/ emergency unit area. Most hospitals did not have the capacity to quarantine large number of patients. The study has also illustrated that there is no model easily available, suitable for the South African context, that can be used by hospital management in facility specific planning for infectious disease outbreaks. Conclusions It can be concluded from the findings of this study that academic hospitals in Gauteng, as well as in other areas of South Africa, are not adequately prepared for the management of an infectious disease outbreak.
Thesis (M Med.(Community Health))--University of Limpopo, 2009.
Keywords: Infectious diseases outbreak